Development and Validation of The Indonesian Family Estrangement Scale (I-FES): DEVELOPMENT AND VALIDATION OF THE INDONESIAN FAMILY ESTRANGEMENT SCALE (I-FES) - Raharjo, Alim Panggih; Ghina Syauqila; Shadillah Ilhami Rez’qi Haryandinny; Alfi Fadli (Psikologi UHAMKA, 2024)
Family becomes the strongest and most intimate social bond. However, family conflict, parental neglect and abuse, and poor parenting are found to be increasing and can lead to children being estranged from their families. Up to now, there is no standardized instrument to assess family estrangement. This study aimed to construct and test the content validity, construct validity, and reliability of the Indonesian Family Estrangement Scale (I-FES). The construction of this scale is based on Scharp's (2017) components of family estrangement. FGD was also carried out to explore behavioral indicators that reflect family estrangement. After content validity test, exploratory factor analysis (EFA) was performed to evaluate the factor structure. Reliability was tested via internal consistency. The pilot version of the scale was tested on 219 unmarried university students. Through EFA, 55 items were found to meet the minimum loading factor spread across four-factor structures (Perceived Cohesion (PC), Connectedness State (CS), Sense of Vertical Responsibility (SVR), and Communication Quality (CQ)). All subscales showed very high reliability (α PC = 0.96; α IS = 0.95; α SVR = 0.91; α CQ = 0.80). The results indicated that the I-FES has excellent psychometric properties. Confirmatory factor analysis is needed as the next stage.